Cerebral microdialysis and glucopenia in traumatic brain injury: A review - Sharma, Himanshu; McGinnis, John P.; Kabotyanski, Katherine E.; Gopinath, Shankar P.; Goodman, Jerry C.; Robertson, Claudia; Cruz Navarro, Jovany (Frontiers in Neurology, 2023)
Traditionally, intracranial pressure (ICP) and partial brain tissue oxygenation (PbtO2) have been the primary invasive intracranial measurements used to guide management in patients with severe traumatic brain injury (TBI). After injury however, the brain develops an increased metabolic demand which may require an increment in the oxidative metabolism of glucose. Simultaneously, metabolic, and electrical dysfunction can lead to an inability to meet these demands, even in the absence of ischemia or increased intracranial pressure. Cerebral microdialysis provides the ability to accurately measure local concentrations of various solutes including lactate, pyruvate, glycerol and glucose. Experimental and clinical data demonstrate that such measurements of cellular metabolism can yield critical missing information about a patient’s physiologic state and help limit secondary damage. Glucose management in traumatic brain injury is still an unresolved question. As cerebral glucose metabolism may be uncoupled from systemic glucose levels due to the metabolic dysfunction, measurement of cerebral extracellular glucose concentrations could provide more predictive information and prove to be a better biomarker to avoid secondary injury of at-risk brain tissue. Based on data obtained from cerebral microdialysis, specific interventions such as ICP-directed therapy, blood glucose increment, seizure control and/or brain oxygen optimization can be instituted to minimize or prevent secondary insults. Thus, microdialysis measurements of parenchymal metabolic function provides clinically valuable information that cannot be obtained by other monitoring adjuncts in the standard ICU setting.